Effects of anesthesia with the essential oil of Ocimum gratissimum L. in parameters of fish stress - L.L. SILVA; Q.I. GARLET; G. KOAKOSKI; T.A. OLIVEIRA; L.J.G. BARCELLOS; B. BALDISSEROTTO; A.M.S. PEREIRA; B.M. HEINZMANN (Universidade Estadual Paulista, 2015)
RESUMO:The effects of anesthesia with the essential oil of Ocimum gratissimum (EOO) in parameters of stress after handling were investigated in silver catfish (Rhamdia quelen). EOO was obtained from the aerial parts by hydrodistillation. Juveniles were anesthetized with 70 or 300 mg L-1 EOO and submitted to air exposure for 1 minute. The fishes were sampled immediately or transferred to anesthetic-free aquaria until sampling. In the first experiment, juveniles had their blood collected at 0, 1, 4, and 8 h after handling to assay plasma cortisol and blood glucose levels. The unanesthetized animals were restrained manually for blood collection. In the second experiment, water samples of the recovery aquaria were collected to evaluate net ion fluxes at 0 - 4 h and 4 - 8 h. Water and ethanol controls were also performed under the same conditions. The results showed that the cortisol levels did not differ among the treatments. Hyperglycemia was verified in fish exposed to 70 and 300 mg L-1 EOO at 1 h and 4 h after handling. After 8 h, cortisol and glucose concentrations were lower or similar than those from immediately after handling for all treatments. EOO anesthesia prevented Na+ efflux observed in the control groups in both flux periods. There were net Cl- and K+ effluxes at 0 - 4 h and influxes at 4 - 8 h after handling in most treatments, and these fluxes did not differ among the treatments. The results suggest that EOO did not impair stress recovery and did not act as an additional handling stressor in silver catfish.